The novel anti-inflammatory activity of mcIRBP from Momordica charantia is associated with the improvement of diabetic nephropathy. Issue 3 (13th January 2022) - Liao, Pei-Yung; Lo, Hsin-Yi; Liu, I-Chen; Lo, Lun-Chien; Hsiang, Chien-Yun; Ho, Tin-Yun
Abstract : Diabetic nephropathy is an inflammatory immune disorder accompanying diabetes. Abstract : Diabetic nephropathy is an inflammatory immune disorder accompanying diabetes. A trypsin inhibitor of Momordica charantia, mcIRBP, is an abundant 68 amino acid residue protein that interacts with the insulin receptor. Here the long-term effects of mcIRBP on the improvement of diabetic nephropathy were determined. Type 2 diabetic mice ( db / db ) were given mcIRBP administered orally for 12 consecutive weeks. Histological changes relating to the kidney were evaluated using Periodic Acid Schiff and Sirius Red staining. The mcIRBP-affected gene expression profile in the kidney was determined using RNA-Seq. The renoprotective mechanism of mcIRBP was elucidated based on ex vivo imaging and immunohistochemistry staining. Data showed that the administration of mcIRBP significantly decreased fasting blood glucose and glycated hemoglobin A1c (HbA1c) levels by 61% and 27.92%, respectively, suggesting that mcIRBP exhibited HbA1c-lowering abilities in diabetic mice. RNA sequencing (RNA-Seq) analysis showed that the majority of the mcIRBP-affected biological pathways were associated with inflammation and immunity, and the nuclear factor-κB (NF-κB) signaling pathway was significantly affected by mcIRBP. Ex vivo imaging showed that mcIRBP significantly decreased NF-κB-driven bioluminescence in the kidney by 46 ± 23%. The levels of the renal function indices, Evans blue dye content, fibrosis lesions, and cytokine expression were significantly decreased by mcIRBP, suggesting that mcIRBP improved vascular leakage and the pathological and inflammatory characteristics of diabetic nephropathy. This is the first study reporting that, in addition to blood glucose regulation, mcIRBP can act as a novel renoprotective and anti-inflammatory polypeptide, thereby improving diabetic nephropathy in db / db mice. In addition, this study suggested that there was a potential medicinal use of mcIRBP for the management of diabetes and its complications.